Sofística e Retórica no Górgias de Platão - Daniel R. N. Lopes (Araucaria)
This essay aims at elucidating the distinction between sophistry and rhetoric in Plato’s Gorgias starting from Socrates’ enigmatic contention that “sophists and rhetors are mixed up in the same area and about the same thing, since they are so close to each other” (465c4-5; Irwin’s translation). To this end I will discuss, firstly, the genealogy of the Greek words sophistikē and rhētorikē in the remaining Greek literature, attempting to show that the modern notions of “sophistry” and “rhetoric” in a broad sense derive from a Platonic-Aristotelian operation of delimitating a special kind of thought and pedagogical activity in opposition to “philosophy”. Secondly, I will analyze some passages of Plato’s Gorgias and Protagoras in which these two notions are being theoretically defined. The general idea pursued in this essay is that rhetoric integrates the sophistic education represented paradigmatically by Protagoras as a necessary means for the citizen to take part in the deliberative institutions of a democratic city (Counsel and Assembly), whereas in the case of Gorgias rhetoric – and more specifically, the judiciary species – consists in the end itself of his pedagogical activity, and not as a means to a wider moral and intellectual education – that is to say, the teaching of political art, identified with moral virtue in Plato’s Protagoras.